AB0100 Identification of the antimicrobial peptide LL-37 as a potential mediator of synovial inflammation in RA. (23rd January 2014) - Neregård, P.; Engström, M.; Lindh, M.; Agerberth, B.; Catrina, A.I.
Abstract : Background: LL-37, a member of the cathelicidin family of host defense peptides, has a broad range of antimicrobial and immunomodulatory effects that potentially can have an impact on the regulation of the adaptive immune system. Objectives: In this study we aimed to investigate a potential role for LL-37 in mediating chronic synovial inflammation. Methods: 49 patients meeting the 1987 American College of Rheumatology (ACR) criteria for RA were recruited for this study. We evaluated LL-37 by immunohistochemistry in synovial biopsy samples obtained before and after a mean of 8 weeks of treatment from 15 patients treated with adalimumab, 12 patients treated with etanercept and 11 patients treated with methotrexate, as well as from 11 patients prior to and 2 weeks after injection with intraarticular glucocorticoids. LL-37 was also evaluated in synovial biopsies obtained from 10 healthy volunteers. Microscopic results were analyzed by double-blind semi-quantitative analysis. Synovial localization of LL-37 was performed by double fluorescent stainings for LL-37 and cell surface markers. LL-37 was detected in synovial fluid by Western blots. Statistical analysis was performed using Wilcoxon test for paired comparisons and Man-Whitney test for comparisons of independent samples. Results: LL-37 was expressed in most of the RA synovial biopsies both in the lining and sublining layers and readily identified in the synovial fluid. Serial and double-fluorescent immunostaining for cell surface markers identifies granulocytes (CD66 positive cells) and macrophages (CD163 positive cells) as main cells expressing LL-37. Inflamed synovial tissue obtained from active arthritis prior to treatment expressed higher levels of LL-37 as compared to healthy individuals. Treatment with adalimumab, etanercept and intraarticular glucocorticoids but not methotrexate resulted in a significant down-modulation of LL-37 expression. Conclusions: Our results demonstrate presence of LL-37 in the context of chronic synovial inflammation and show specific regulation of this molecule by distinct anti-rheumatic agents. Further investigation to reveal the functional consequences of our findings on synovial antimicrobial and inflammatory activity is needed. Disclosure of Interest: None Declared